2017
DOI: 10.3389/fendo.2017.00081
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Insulin Injection Modalities: Effects on Hepatic and Hippocampal Expression of 11β-Hydroxysteroid Dehydrogenase Type 1 in Juvenile Diabetic Male Rats

Abstract: BackgroundDysregulation of the hypothalamic–pituitary–adrenal (HPA) axis is often encountered in diabetes, leading to several clinical complications. Our recent results showing an elevated tetrahydrocortisol/tetrahydrocorticosterone ratio in morning urine of diabetic children compared to that of controls suggest an increased nocturnal activity of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) in the former.QuestionWe hypothesized that these observations could be explained by a reduced inhibition of hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Given our data in T1D children [137], we hypothesized that 11β-HSD1 may also be overactivated in brain of T1D and be responsible for cognitive impairments as it is the case in old individuals. We demonstrated that 11β-HSD1 levels were increased in T1D juvenile rats hippocampus [50,51]. These studies point to a pivotal role for 11β-HSD1 in glucocorticoid excess induced by T1D and consequently of altered hippocampal function (performance on the Y-maze and recognition of a displaced object [51]).…”
Section: Bioavailability Of Glucocorticoids: the Enzyme 11ß-hsd1supporting
confidence: 53%
See 1 more Smart Citation
“…Given our data in T1D children [137], we hypothesized that 11β-HSD1 may also be overactivated in brain of T1D and be responsible for cognitive impairments as it is the case in old individuals. We demonstrated that 11β-HSD1 levels were increased in T1D juvenile rats hippocampus [50,51]. These studies point to a pivotal role for 11β-HSD1 in glucocorticoid excess induced by T1D and consequently of altered hippocampal function (performance on the Y-maze and recognition of a displaced object [51]).…”
Section: Bioavailability Of Glucocorticoids: the Enzyme 11ß-hsd1supporting
confidence: 53%
“…In response to a restraint stress, the peak of secretion of corticosterone was similar between experimental groups, contrary to the recovery that was delayed in untreated diabetic rats [51], suggesting an impaired feedback mechanism as described in humans. Although insulin treatment prevented the increased levels of corticosterone in basal conditions, there was no beneficial effect under stress conditions [50]. Within hippocampus, corticosterone concentration was also increased at the nadir in untreated diabetic rats, as well as 11β-HSD1 activity.…”
Section: T1dmentioning
confidence: 91%
“…was rejected because 11β-HSD1 activity increased in healthy adults submitted to a hyperinsulinaemic euglycaemic clamp ( 20 ). However, in a rodent model of insulin-deficient diabetes, we showed that intraperitoneal insulin led to a decrease in 11β-HSD1 activity in the liver, whereas subcutaneous insulin did not ( 11 ). At the cellular level, results are contradictory regarding whether glucose control (via insulin administration) has a direct ( 21 ) or indirect inhibitory effect ( 22 ) on 11β-HSD1 transcription or activity.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, we showed that glucocorticoid levels and 11β-HSD1 activity were elevated in diabetic rats not treated with insulin. Subcutaneous administration of insulin partially prevented glucocorticoid dysregulation by decreasing 11β-HSD1 activity in the liver ( 11 ). We also showed that insulin treatment partially rescued several hippocampus-dependent behavioural and structural changes in early onset insulin-deficient diabetic rats, as well as 11β-HSD1 activity in the hippocampus ( 12 ) indicating that the elevated bioavailability of glucocorticoids may be involved in the diabetes cognitive dysfunctions.…”
Section: Introductionmentioning
confidence: 99%